Developing Cognitive Skills in Number Recognition Through Picture Number Card Media in Early Childhood - Mahrus, Mahrus (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Cognitive abilities are the brain-based skills required to perform any task from the simplest to the most complex. Children's ability to recognize numbers requires thinking about objects, objects, or events. The aims of this study were: 1) To find out the teacher's planning in developing cognitive abilities in introducing numbers using picture number cards to student A at PAUD Permata Jember. 2) To find out the form of teacher implementation in developing cognitive abilities in introducing numbers with illustrated number cards media to group A students at PAUD Permata Jember. 3) To determine the teacher's evaluation in developing cognitive abilities in introducing numbers with illustrated number card media to group A students at PAUD Permata Jember. This research uses a qualitative approach with the type of case study research. This research used observation, interviews, and documentation as data collection techniques. Data analysis uses data condensation, data presentation, and data verification. In comparison, the validity of the data is used in triangulation techniques and data sources. Based on the study's results, 1) planning: Formation of themes, preparation of lesson plans, preparation of learning media, choice of teaching methods and materials to be implemented, and provision of information to students before learning activities. 2) Forms of implementation: opening activities, namely greetings, praying, and asking how students are doing; Second is the core activity, namely seating management, singing songs about number recognition, distributing illustrated number card media to students, implementing number recognition, students individually take turns demonstrating on the blackboard. Then, the third is the closing activity, namely, the teacher instructs (recalling) the repetition of today's learning activities, and the last is the closing activity of learning (praying). 3). evaluation, observation (observation), performance (assignment), and checklist.